Graph-QL Responsibility Analysis at Integrated Competency Certification Test System Base on Web Service - Masdiyasa, I Gede Susrama; Budiwitjaksono, Gideon Setya; M, Hafidz Amarul; Sampurno, Ilham Ade Widya; Mandenni, Ni Made Ika Marini (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2020)
Graph-QL (Graph Query Language) is a new concept in API development. Graph-QL was developed by Facebook which is implemented on the server side. Although Graph-QL is a query language, Graph-QL is not directly related to the database, in other words Graph-QL is not limited to certain databases both SQL and NOSQL. The position of Graph-QL is on the client and server side that accesses an API. One of the goals of developing this query language is to facilitate data communication between backend and frontend / mobile applications. For this reason, the responsibility of Graph-QL in terms of response time and response size will be tested by the creation of an integrated system of competency certification testing, which is based on web service and compared to the efficiency and flexibility by using the REST API. From the test results it was found that Graph-QL has advantages in presenting data on the server and REST API has a better performance in response speed .